Colloid-Chemical Properties And Antimicrobial Activities Of New Biological Surface Active-Substances (Eurasian Research Bulletin, 2024)
The new biological surface active-substances were obtained from microbial cultural liquids and medical plants. The obtained surface active-substances were purified using solvents, distillation and recrystallisation methods. The physical and colloid-chemical properties, and antimicrobial activities of new biological surface active-substances have been investigated. A good correlation between the foam forming ability and the surface activity of new biological surfactants has been determined. It has been shown, that the stability of surfactant foams significantly determined by the interaction of surfactant molecules in the monolayer. The antimicrobial activityes of new biological surfactants were investigated. The obtained results showed the very good effectiveness of new biological surfactants against microorganisms.